2007
DOI: 10.4161/cc.6.14.4493
|View full text |Cite
|
Sign up to set email alerts
|

Bub1: Escapades in a Cellular World

Abstract: The spindle assembly checkpoint is an important surveillance mechanism that ensures high fidelity mitotic chromosome segregation. This is accomplished by monitoring whether sister chromatids lack tension or attachment to spindle microtubules. It is mediated by checkpoint complexes or individual proteins that inhibit the ubiquitin ligase activity of the anaphase-promoting complex/cyclosome (APC/C) via targeting of the Cdc20 regulatory subunit. The Bub1 kinase is a key spindle checkpoint regulatory protein. Bub1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 72 publications
0
35
0
Order By: Relevance
“…Warren et al (39) previously observed that bub1 mutants had about 10-fold higher chromosome loss rates than mad2 strains and suggested that Bub1p (but not Mad2p) had a role in chromosome segregation in the absence of induced spindle damage. A variety of experiments have indicated that Bub1p is important in establishing the correct inner and outer kinetochore structures (40), and cells with low levels or no Bub1p have defective associations between the kinetochore and microtubules, decreased levels of chromosomes that are bioriented at the spindle, and decreased sister chromatid cohesion at the centromere (41). Thus, loss of Bub1p (unlike the loss of Mad2p) leads to defects in the mechanics of chromosome segregation in addition to defects in the SAC, resulting in very high levels of aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…Warren et al (39) previously observed that bub1 mutants had about 10-fold higher chromosome loss rates than mad2 strains and suggested that Bub1p (but not Mad2p) had a role in chromosome segregation in the absence of induced spindle damage. A variety of experiments have indicated that Bub1p is important in establishing the correct inner and outer kinetochore structures (40), and cells with low levels or no Bub1p have defective associations between the kinetochore and microtubules, decreased levels of chromosomes that are bioriented at the spindle, and decreased sister chromatid cohesion at the centromere (41). Thus, loss of Bub1p (unlike the loss of Mad2p) leads to defects in the mechanics of chromosome segregation in addition to defects in the SAC, resulting in very high levels of aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…The most straightforward scenario might be that LT acts as a molecular scaffold to connect Bub1 with its substrate p53. However, as we recently showed, purified recombinant Bub1 phosphorylates only p53 on Ser37 in vitro but not on the other sites (65). Moreover, Bub1 RNA interference could block only Ser37 phosphorylation.…”
Section: Vol 83 2009 Sv40 T-antigen-induced Dna Damage Response Viamentioning
confidence: 99%
“…5 Cells with a partial or complete loss of the aforementioned crucial molecules of the mitotic checkpoint manifest insufficient mitotic arrest, chromosome missegregation, abnormal DNA ploidy, senescence, cell death, and cellular transformation. [7][8][9][10] Intriguingly, an overactive mitotic checkpoint also leads to mitotic cell death, chromosome missegregation, and aneuploidy. [11][12][13][14] To illustrate the participation of MTBP in cell cycle regulation and to understand the underlying molecular mechanism, we examined the effects of modulating MTBP expression on cell cycle progression.…”
mentioning
confidence: 99%